Bamboo diversity in Weh Island, Aceh, Indonesia - MUHAMMAD AZLI RITONGA; SYAMSUARDI SYAMSUARDI; NURAINAS NURAINAS; I PUTU GEDE P. DAMAYANTO (Society for Indonesian Biodiversity, 2023)
Abstract. Ritonga MA, Syamsuardi, Nurainas, Damayanto IPGP. 2023. Bamboo diversity in Weh Island, Aceh, Indonesia. Biodiversitas 24: 2563-2576. Bamboo is an important plant resource in Indonesia, whose inventories were mostly conducted on the main islands. In contrast, the inventory for small islands, such as Weh Island in Northern Sumatra, has never been done. Weh Island, however, is an atoll island that has been raised above sea level and is suspected to have a unique diversity of flora, especially bamboo. This study aimed to understand the diversity of bamboo on Weh Island. Fieldwork was conducted in August-September 2022 in Weh Island, Aceh, Indonesia. Bamboo specimens were collected by collecting flora diversity method and deposited in Herbarium Andalas and Herbarium Bogoriense. Morphological characteristics were observed to identify and arrange species descriptions and as a determination key. The spatial distribution of bamboo was analyzed using QGIS software and overlaid with a land cover and altitude map. We also performed a similarities analysis using morphological characteristic. There are eight species of bamboo on Weh Island: Bambusa multiplex (Lour.) Raeusch. ex Schult.f., Bambusa spinosa Roxb., Bambusa tuldoides Munro,Bambusa vulgaris Schrad. ex J.C.Wendl., Dendrocalamus asper (Schult.f.) Backer, Schizostachyum brachycladum (Kurz ex Munro) Kurz, Schizostachyum silicatum Widjaja, and Thyrsostachys siamensis Gamble. B. vulgarisis most abundant and widespread on Weh Island; meanwhile, B. multiplexand B. tuldoidesare the least common. The presence of S. silicatum on Weh Island and Bangka Island was additional information on the expansion of these species distributions outside the mainland of Sumatra. Bamboos on Weh Island were found around settlements, plantations, and forests at 1 to 212 m asl. Bamboo species on Weh Island can be clustered into four groups based on their morphological characteristics.